2010
DOI: 10.1007/s11258-010-9863-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity in ecosystem structure and productivity in a moist Kenyan savanna

Abstract: Topographic variations and disturbances are key sources of spatial heterogeneity in the ecosystem and may influence its functioning, productivity, and carbon (C) storage. In water controlled ecosystems, structural and functional heterogeneity become distinct during drought when the ecosystem processes are operating at their limits. We examined spatial heterogeneity arising from grazing, abandoned cropland, presence of Acacia trees, and termite mounds (termitaria). Soil water content (SWC) was significantly (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The composition of herbaceous vegetation varied considerably within our study sites irrespective of rainfall treatment, which characterises the heterogeneity of Lambwe valley (Allsopp and Baldry, 1972). Spatial variation in the composition of herbaceous species may be attributed to the ability of individual species to adapt to local and edaphic conditions (Silva et al., 2013, Augustine, 2003), which are different within our sites (Otieno et al., 2011). It is possible that the lower vegetation dominance in the grazed plots (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The composition of herbaceous vegetation varied considerably within our study sites irrespective of rainfall treatment, which characterises the heterogeneity of Lambwe valley (Allsopp and Baldry, 1972). Spatial variation in the composition of herbaceous species may be attributed to the ability of individual species to adapt to local and edaphic conditions (Silva et al., 2013, Augustine, 2003), which are different within our sites (Otieno et al., 2011). It is possible that the lower vegetation dominance in the grazed plots (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…This is even more so as a review of the small mammal inventories in KNP based on published reports had indicated higher species richness for woodlands (Namukonde et al, in press). Miombo is considered a vegetation formation growing on poor soil and thus not being very productive (East, 1984;Desanker, Frost, Justice, & Scholes, 1997;Campbell et al, 2007), while termitaria are characterized by good soil conditions that promotes plant growth (Otieno et al, 2011). While high productivity soil results in high biomass across trophic levels, the link between productivity and species diversity remains unclear despite decades of research and seems to depend on local conditions, including habitat structure that is likely to obscure productivity-diversity relationships when considered across different vegetation types (Liang et al, 2016, Simons et al, 2017Socher et al, 2012Socher et al, , 2013Srivastava & Lawton 1998).…”
Section: Discussionmentioning
confidence: 99%
“…NMDS integrates community measures, that is, dissimilarity, diversity, and abundance to generate matrices. Differences in species composition between vegetation types and fire effects were determined by permutational multivariate analyses of variance (perMANOVA) used in the function adonis() in R package vegan (Oksanen et al, 2015). The analyses were based on community dissimilarity matrices by calculating Bray-Curtis dissimilarities of relative abundance data (Nopper, Ranaivojaona, Riemann, Ro¨del, & Ganzhorn, 2017).…”
Section: Fire Agementioning
confidence: 99%
“…Rainfall is bimodal, peaking in April–June and September–November. The annual dry and hot period is from January to March [ 21 ]. The community in Lambwe Valley practice subsistence farming, fishing, and animal husbandry.…”
Section: Methodsmentioning
confidence: 99%